Avaliação na Educação Infantil: entrecruzando olhares para ressignificar instrumentos - Machado, Priscila de Freitas (Universidade Federal do Tocantins, 2023)
The present study is linked to the research line Specific Curriculum of Stages and Modalities of Education, of the Professional Graduate Program in Education at the Federal University of Tocantins, in the area of concentration Teaching and Learning. It aims to analyze how the teachers of a Municipal Center for Early Childhood Education (CMEI) in the municipality of Aparecida do Rio Negro-TO perceive the evaluation process of children in their pedagogical practice, in order to support the construction of a proposal for a recording instrument and assessment of development and learning. Understanding assessment as an inseparable part of pedagogical practice, in a mediating perspective whose purpose is decision-making to favor the child's learning without anticipating elementary school practices, an attempt was made to answer the following questions: how do these professionals conceive assessment in this context? stage of education? How are the evaluation practices of these teachers characterized in relation to the child's development and learning? What are the possible relationships between the evaluation practices carried out by the teachers and the teaching-learning process they develop? Methodologically, the investigation is characterized as a qualitative study and used bibliographical, documentary and empirical research through a case study that sought to apprehend the conceptions of the teachers of a CMEI in Aparecida do Rio Negro-TO about the evaluation process, from of interviews with eight teachers who work in the nursery and preschool classes, as well as consultation of documents, such as the evaluation registration forms used in early childhood education. Through the analysis of the data collected and presented in the sections of this text, advances and difficulties faced by teachers in the process of evaluating students were verified, as well as the relationships established between the act of evaluating and their pedagogical practices, highlighting the evaluation instruments used in this process. The survey results indicate the need for instruments and evaluation procedures specific to early childhood education. Thus, when we intertwine the meanings attributed by the teachers to the legal bases and theoretical conceptions about assessment in early childhood education, we present the Learning Path assessment instrument, which involves recording and monitoring the pedagogical work on an ongoing basis. The research presents itself as a possibility to broaden the discussions on the evaluation in early childhood education, in the search to advance in the aspects that are still necessary, in order to get closer and closer to the provision of a quality education for young children.